1988
DOI: 10.3109/00016488809119507
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Differentiation-inducing Agents and Conventional Drugs in Head and Neck Cancer Xenografts

Abstract: Three putative differentiation inducing agents and five conventional drugs which have been shown to be active in patients with squamous cell carcinoma of the head and neck (HNSCC), were tested for activity against HNSCC transplanted in nude mice. Drugs were administered at a maximum tolerated dose level. By testing the effect of conventional drugs the value of the nude mouse xenograft model for testing new drugs was assessed. Bleomycin as well as cisplatin showed antitumour effects in nude mice, although toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Their results showed that the model might be of value in the detection of new anticancer drugs, although it may have a tendency to underestimate the activity of some drugs. 139 A significant disadvantage to the xenograft animal model is that less than 2% of human tumor explants metastasize when placed subcutaneously in nude mice. 140 Increased concentrations of NK cells in nude mice may explain resistance to metastasis.…”
Section: Nude Mouse Models-subcutaneous Ectopic Xenotransplantationmentioning
confidence: 99%
“…Their results showed that the model might be of value in the detection of new anticancer drugs, although it may have a tendency to underestimate the activity of some drugs. 139 A significant disadvantage to the xenograft animal model is that less than 2% of human tumor explants metastasize when placed subcutaneously in nude mice. 140 Increased concentrations of NK cells in nude mice may explain resistance to metastasis.…”
Section: Nude Mouse Models-subcutaneous Ectopic Xenotransplantationmentioning
confidence: 99%
“…Next to in vitro models for cancer research, HNSCC xenograft mouse models, which mimic the physiological and pathophysiological complexity of tumors, were already introduced more than 30 years ago ( 37 39 ). For many years these models represent the industrial gold standard for the development of cytotoxic cancer therapies and targeted therapies and for monitoring their efficacy employing human cancer cell lines/tumor tissues engrafted into immunocompromised mice to evaluate pharmacology, efficacy, and safety profiles of the agents to be tested ( 40 – 42 ).…”
Section: In Vivo Models—advantages Disadvantages and Ethical...mentioning
confidence: 99%